Kontribusi KH. Abdul Wahid Hasyim Dalam Dunia Pendidikan - Mulyanto Abdulloh Khoir; Aulia Arsinta; Ikke Fitriana Nugrahini (4, 2024)
Education is a fundamental aspect in advancing a country, including religious education which plays a significant role in forming the character of individuals and society. This article discusses the thoughts and contributions of KH. Abdul Wahid Hasyim in developing the Islamic education curriculum in Indonesia. KH. Abdul Wahid Hasyim, a prominent cleric, succeeded in combining religious education and general education in Islamic boarding schools, making him a pioneer of modern education in Islamic boarding schools. He introduced the classical system, speech courses, and foreign languages ​​such as Dutch and English. The emphasis on inclusivity, tolerance, and lifelong education are characteristic of his thinking. This research uses qualitative methods with observation techniques and literature data collection. The research results show that KH. Abdul Wahid Hasyim is very relevant to today's education, especially in character formation, tolerance and inclusiveness. His contributions include developing a curriculum based on religious values, character building, and promoting the values ​​of tolerance. KH's thoughts. Abdul Wahid Hasyim provides valuable insights for the development of an education system that is holistic and relevant to the demands of the times. Abstrak Pendidikan merupakan aspek fundamental dalam memajukan suatu negara, termasuk di dalamnya pendidikan agama yang memainkan peran signifikan dalam pembentukan karakter individu dan masyarakat. Artikel ini membahas pemikiran dan kontribusi KH. Abdul Wahid Hasyim dalam pengembangan kurikulum pendidikan Islam di Indonesia. KH. Abdul Wahid Hasyim, seorang ulama terkemuka, berhasil memadukan pendidikan agama dan pendidikan umum dalam pesantren, menjadikannya perintis pendidikan modern di pesantren. Beliau memperkenalkan sistem klasikal, kursus pidato, serta bahasa asing seperti Belanda dan Inggris. Penekanan pada inklusivitas, toleransi, serta pendidikan seumur hidup merupakan ciri khas pemikirannya. Penelitian ini menggunakan metode kualitatif dengan teknik observasi dan pengumpulan data literatur. Hasil penelitian menunjukkan bahwa pemikiran KH. Abdul Wahid Hasyim sangat relevan dengan pendidikan masa kini, terutama dalam pembentukan karakter toleransi, dan inklusivitas. Kontribusi beliau mencakup pengembangan kurikulum yang berlandaskan nilai-nilai agama, pembentukan karakter, dan promosi nilai-nilai toleransi. Pemikiran KH. Abdul Wahid Hasyim memberikan pandangan berharga bagi pengembangan sistem pendidikan yang holistik dan relevan dengan tuntutan zaman.